Lateral arm plate morphology in brittle stars (Echinodermata: Ophiuroidea): new perspectives for ophiuroid micropalaeontology and classification. Zootaxa, 3013: 1–47. (Erratum) - Thuy, B.; Stöh, S. (Zootaxa, 2012)
Erratum